first-order nonlinear ordinary differential equation.
1-step:
Solve "x+2y(x)-1=(x+2y(x)+1)\\tfrac{dy(x)}{dx}"
2-step:
Let "v(x)=x+2y(x)," which gives "\\tfrac{dv(x)}{dx}=2\\tfrac{dy(x)}{dx}+1:"
"v(x)-1=\\tfrac{1}{2}(\\tfrac{dv(x)}{dx}-1)(v(x)+1)"
3-step:
Solve for "\\tfrac{dv(x)}{dx}:"
"\\tfrac{dv(x)}{dx}=\\tfrac{3v(x)-1}{v(x)+1}"
4-step:
Divide both sides by "\\tfrac{3v(x)-1}{v(x)+1}" :
"\\tfrac{\\tfrac{dv(x)}{dx}(v(x)+1)}{3v(x)-1}=1"
5-step:
Integrate both sides with respect to x:
"\\int" "\\tfrac{\\tfrac{dv(x)}{dx}(v(x)+1)}{3v(x)-1}dx=\\int1dx"
6-step:
Evaluate the integrals:
"\\tfrac{1}{9}(4log(3v(x)-1)+3v(x)-1)=x+C_{1}"
where "C_{1}" is an arbitrary constant.
7-step:
Solve for "v(x):"
"v(x) = \\tfrac{1}{3}(4W(- \\tfrac{1}{4} \\sqrt[4]{e^{9(x+C_{1})}})+1" )
or
"v(x) = \\tfrac{1}{3}(4W(- \\tfrac{1}{4}i \\sqrt[4]{e^{9(x+C_{1})}})+1)"
or
"v(x) = \\tfrac{1}{3}(4W( \\tfrac{1}{4}i \\sqrt[4]{e^{9(x+C_{1})}})+1)"
or
"v(x) = \\tfrac{1}{3}(4W( \\tfrac{1}{4} \\sqrt[4]{e^{9(x+C_{1})}})+1)"
8-step:
Substitute back for "y(x) =" "\\tfrac{1}{2}(-x+v(x)):"
Answer:
"y(x) = \\tfrac{1}{6}(-3x+4W(- \\tfrac{1}{4} \\sqrt[4]{e^{9(x+C_{1})}})+1)"
or
"y(x) = \\tfrac{1}{6}(-3x+4W(- \\tfrac{1}{4}i \\sqrt[4]{e^{9(x+C_{1})}})+1)"
or
"y(x) = \\tfrac{1}{6}(-3x+4W( \\tfrac{1}{4}i \\sqrt[4]{e^{9(x+C_{1})}})+1)"
or
"y(x) = \\tfrac{1}{6}(-3x+4W(\\tfrac{1}{4} \\sqrt[4]{e^{9(x+C_{1})}})+1)"
"y(x)=\\tfrac{2}{3}(W(-e^{\\tfrac{9x}{4+C_{1}-1}})+1)+\\tfrac{1}{2}(-x-1)."
Comments
Leave a comment